PEMBELAJARAN BERBASIS SOSIOKULTURAL PADA TEMA LINGKUNGAN BERSIH SEHAT DAN ASRI DI SEKOLAH DASAR - Putri Zudhah Ferryka (Jurnal Pena Karakter, 2019)
The quality education in Indonesia need to be increased balancing between technology and knowledge. One of the way to increasing is the quality of education. The process of education is centered in students as a subjects of education. The teacher is the main of potency, creativity and motivation to theirs students to increasing the process of learning. Learning based on society said that society is important things in process of students learning. Social environment and culture is important things in this method. Social interaction between students and society helpful students to be better in education. Teacher can help social environment to make education process becomes better. The implication of teaching and learning process is in theme are social environment clean and healthy to make the class being more interactive and the process of learning to be more responsibility. So the process of teaching and learning able to construct between knowledge and all participant in this process.